Finnish Muslim and Protestant Background Youth's Discourses on Religion and Religious Commitment. Issue 3 (3rd July 2019) - Kimanen, Anuleena
Abstract: This article compares discourses on religion and religious commitment of Muslim and Protestant background young people in the Finnish capital region. It is based on 12 interviews of 19 teenagers, which are analyzed following Fairclough's stages of discourse analysis. The analysis shows that the Muslim background youth position themselves as insiders, whereas most of the Protestant background youth distance themselves from religion, although not totally. The Protestant background youth position themselves as autonomous individuals somewhat consistently, whereas the Muslim background youth emphasize their autonomy only when talking about instructions given by the school. These differences are bound to affect classroom interaction.